Letter - Hodgkinson, George Edward
037-0118-001 TELEPHONE 2988 COVENTRY LABOUR PARTY. Affiliated to the National Labour Party President — Coun. S. STRINGER Vice-President Coun. V.A. Hammond. Financial Secretary Coun. R.W. Harris Secretary and Agent Coun. Geo. E. Hodgkinson Objects The establishment of the Co-operative Commonwealth. Offices: Barbican Chambers, Earl Street, COVENTRY. 19th June 1937. Mr. Walter Citrine. Secretary T.U.C.G.C. Transport House, Smith Square. LONDON.S.W.1. Dear Comrade., The Spanish Aid Committee of Coventry for whom I am acting as one of the Joint Secretaries have requested me to enquire if it were possible for a Party of Coventry members to visit the Camp established at Southampton for the Spanish children who have been evacuated from Bilbao. Will you kindly let me know if it is possible to arrange a visit. Yours fraternally George E. Hodgkinson Joint Secretary. Tell Irwin 292/946/37/118